2018
DOI: 10.3390/s18093051
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Shade-Matching Device for Dental Color Determination Using the Support Vector Machine Algorithm

Abstract: In this study, we developed a digital shade-matching device for dental color determination using the support vector machine (SVM) algorithm. Shade-matching was performed using shade tabs. For the hardware, the typically used intraoral camera was modified to apply the cross-polarization scheme and block the light from outside, which can lead to shade-matching errors. For reliable experiments, a precise robot arm with ±0.1 mm position repeatability and a specially designed jig to fix the position of the VITA 3D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 37 publications
0
47
0
1
Order By: Relevance
“…[ 12 ] Kim et al . [ 11 ] developed the method of digital shade by modifying the intraoral camera. The two linear polarizer were placed in front of the light source (cross-polarization) of an intraoral camera which blocks the light from outside.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 ] Kim et al . [ 11 ] developed the method of digital shade by modifying the intraoral camera. The two linear polarizer were placed in front of the light source (cross-polarization) of an intraoral camera which blocks the light from outside.…”
Section: Discussionmentioning
confidence: 99%
“…They further stated that spectrophotometer and colorimeters do not provide true image information to measure the exact value of tooth color. [ 11 ] A cross-sectional study on 400 individuals reported that the most common shade of maxillary and mandibular incisors in younger age male is A2 for Vita Lumina, 2R2.5 for Vita 3D master, and 140 for Chromascop shade guide and for females is A1 for Vita Lumina, 1M2 for Vita 3D master, and 120 for Chromascop shade guide. In the advanced age group, the most common shade for the same teeth is A2 for Vita Lumina, 2R2.5 for Vita 3D master, and 140 for Chromascop shade guide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But still below the accuracy of the reference spectrophotometer system [10] lighting conditions, and results showed that the intraoral scanner obtained a significant higher mean repeatability of dental shade matching compared to the visual method [20]. Kim, et al, developed a digital shade-matching device utilising a modified intraoral camera to measure 3D shade tabs, which reported more than 90% matching accuracy and less than 1% failure rate [21].…”
Section: Shade Matching From Visual To Digitalmentioning
confidence: 99%
“…17 In another reported work, the digital shade matching device for dental colour determination was adopted to identify the optimal solution for quantitative tooth colour measurement. 18 The above literature suggests that machine learning has huge potential for the frontend classification of the multifunctional sensor but the study towards it remains unexplored.…”
Section: Introductionmentioning
confidence: 99%